Manajemen Full Day School dalam Meningkatkan Karakter Religius Peserta Didik di MI Muhammadiyah 04 Ngesong Lamongan - Roudlotul Fikriyah; Ahmad Hariyadi (Departement of Mathematics Education, 2024)
This research aims to analyze full day school management in improving the religious character of students at MI Muhammadiyah 04 Ngesong Lamongan. This research has the following objectives: 1) Explaining the planning of full day school in improving the religious character of students at MI Muhammadiyah 04 Ngesong, 2) Explaining the implementation of full day school in improving the religious character of students at MI Muhammadiyah 04 Ngesong, 3) Explaining the full evaluation day school in improving the religious character of students at MI Muhammadiyah 04 Ngesong. This research uses a qualitative approach with a type of descriptive research, where researchers must understand the phenomena that occur and go into the field to see actual environmental conditions directly. The data collection methods used were observation, interviews and documentation. Data analysis was carried out using the interactive analysis model from Miles and Huberman which involved the process of data reduction, data presentation, and drawing conclusions. The results of this research show that 1) Planning for full day school at MI Muhammadiyah 04 Ngesong to improve students' religious character was carried out through several stages, such as establishing the school's vision, mission and goals, evaluating the current condition and potential of the school, identifying supporting and inhibiting factors, and designing programs. 2) The implementation of full day school in improving students' religious character is divided into learning activities and activities outside of learning. 3) Evaluation of full day school in improving students' religious character is carried out through several aspects, such as context, input, process and product.